Keandalan Papan Lapis dari Kayu Damar (Agathis loranthifolia Salisb.) Terpadatkan sebagai Pelat Buhul pada Arsitektur Konstruksi Atap Kayu The Strength of Densified Agathis (Agathis loranthifolia Salisb.) Plyboard as Gusset in Wood Roof Construction - Rilatupa, James; Surjokusumo, Surjono; Nandika, Dodi (Jurnal Ilmu dan Teknologi Kayu Tropis, 2004)
The aim of this research is to know the densified agathis plyboard characteristics and reliability is used for semi isotropic gusset in wood roof construction, and also to look for suitable models of its connectors for roof construction. The material use for this research is agathis board with dimension of 36 cm (L) x 12 cm (T) x 2 cm (R). This board has been densified until it reached 1 cm in thickness (R). Glue used for this research is epoxy with the trade name Eurepox-710 (resin) and mixed with Euredur-140 (hardener). The bolt used for the testing of embedded strength is bolt St.37 with diameter of 11.12 mm.The result showed that densification could increase physical nature and mechanical strength. The physical nature and mechanical strength also indicated that densified agathis board could be used as gusset in wood roof construction. Results of bolt embedded strength and its ANOVA showed that the gusset of densified agathis plyboard will be reliable for each connection angles, and indicated that the Hankinson theory could not be implemented to forecast the bolt embedded strength for another connection angles. Based on questioners model of the gusset will revealed which is in accordance with the roof construction as issued for the second drawing of the gusset for each connection type. This model has been considered to posses aesthetical and harmonically features wood roof construction of a building